THE USE OF VIDEO AS A SUTURING SKILLS LEARNING RESOURCES IN MEDICAL EDUCATION: A LITERATURE REVIEW - Mega Pandu Arfiyanti (Universitas Muhammadiyah Semarang, 2017)
Using video in learning showed effective results in practicing clinical skills. Video can also be used to teach the clinical practice and physical examination skills. This literature review paper describes the effectiveness of the use of video as a suturing skills learning resources. We search the journal as a review of the literature through Google Scholar and ScienceDirect by using the term or key word search asfollows